A method for preparing a micro-passive electroluminescent electric field sensing patch with vector perception capability and application thereof

CN122652099APending Publication Date: 2026-08-28CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610568204.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-27
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

主要缺陷:(1)材料激发阈值仍高达>0.8 kV/mm,弱场检测能力不足;(2)仅能实现单向(单轴)电场响应,缺乏对电场矢量方向的感知能力;(3)动态范围有限(通常<0.6 kV/mm),且高场强下响应易饱和

Benefits of technology

[0052] Threshold Breakthrough: By leveraging the local electric field enhancement effect of zinc oxide whiskers, the material's luminescence excitation threshold is reduced to 0.2 kV/mm (75% lower than traditional materials), achieving accurate detection of weak field strength (<0.3 kV/mm) for the first time, making it suitable for high-sensitivity scenarios such as partial discharge monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122652099A_ABST
    Figure CN122652099A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a micro passive electroluminescent electric field sensing patch with vector perception capability, and comprises the following steps: S1, preparing ZnS:Cu@Al2O3 particles; S2, mixing 28-32 parts by mass of the ZnS:Cu@Al2O3 particles, 4-6 parts by mass of ZnO whiskers and 95-105 parts by mass of an E51 epoxy resin matrix, adding 80-90 parts by mass of MHHPA as a curing agent and 0.5-1.5 parts by mass of DMP-30 as an accelerator, performing high-speed stirring and dispersion on the mixture, and then performing pre-curing and complete curing, so that a composite material film is finally formed; and S3, using a micro-nano lithography technology to prepare a sensing patch based on the composite material film obtained in the step S2. Through the local electric field enhancement effect of the zinc oxide whiskers, the application realizes the precise detection of a weak field for the first time, and is suitable for high-sensitivity scenes such as partial discharge monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electric power, specifically to a miniature passive electroluminescent electric field sensing patch with vector sensing capability and its preparation method. Background Technology

[0002] As a core physical quantity characterizing the operating state of a power system, the accurate measurement of the electric field is a crucial foundation for achieving the digitalization, intelligentization, and safe and reliable operation of the power grid, directly impacting core aspects such as fault early warning, insulation assessment, and electromagnetic environment monitoring. With the in-depth development of ultra-high voltage transmission technology, large-scale grid connection of new energy sources, and smart grids, the operating environment of power equipment exhibits complex characteristics such as strong electromagnetic interference, strict spatial constraints, and multidimensional state parameters. This creates an urgent need for electric field sensing technology to achieve miniaturization, passivity, high interference immunity, wide dynamic range, and vector sensing capabilities. However, existing mainstream technologies (such as integrated waveguide electro-optic sensors, piezoelectric-photoelectric hybrid sensors, and electrostatically coupled MEMS devices) still face significant challenges in practical applications under complex electromagnetic field environments: complex structures lead to high installation and maintenance costs; the sensing mechanism is sensitive to environmental disturbances (temperature drift, humidity changes, strong electromagnetic noise), and measurement stability and repeatability are prone to degradation; and the reliance on external power supply (light source or circuit) limits their application potential in wide-area passive monitoring networks due to power consumption and lifespan issues.

[0003] Existing Solution 1: Copper-doped zinc sulfide alumina-coated particle sensor: This solution achieves copper ion-doped zinc sulfide lattice through solid-state sintering and utilizes alumina vapor phase coating to improve the insulation and stability of the material. Its core advantage lies in realizing passive electric field-optical signal conversion using the electroluminescence effect. Main drawbacks: (1) The material excitation threshold is still as high as >0.8 kV / mm, resulting in insufficient weak field detection capability; (2) It can only achieve unidirectional (uniaxial) electric field response and lacks the ability to sense the direction of the electric field vector; (3) The dynamic range is limited (usually <0.6 kV / mm), and the response is prone to saturation under high field strength.

[0004] Existing Solution 2: Optical Sensor Based on Electroluminescent Lines: This solution utilizes the luminescence characteristics of electroluminescent lines under the action of an electric field for measurement. Main drawbacks: (1) It requires external driving circuit power supply, is not truly passive, and has power consumption issues; (2) The system structure is relatively complex and has low integration; (3) The dynamic range is narrow (<0.6 kV / mm), making it difficult to cover wide-range application scenarios; (4) It also lacks vector sensing capability.

[0005] The current electromagnetic field sensing technology faces the following core bottlenecks in complex electromagnetic environments:

[0006] 1. High excitation threshold constraint: Sensitivity defects in low field strength environments

[0007] The activation threshold of mainstream electroluminescent materials (such as zinc copper sulfide dopants) is generally higher than 0.8 kV / mm. This characteristic severely limits their applicability in weak field strength scenarios such as monitoring local field strength gradients in power equipment and identifying early insulation defects. For example, in ultra-high voltage transmission systems, the local field strength gradient at the surface of insulators or cable joints may be as low as 0.2 kV / mm, while traditional materials require a high intensity >0.8 kV / mm to trigger the luminescence response, resulting in insufficient detection sensitivity and difficulty in capturing weak field strength fluctuations. In addition, the high excitation threshold also restricts the sensor's real-time response capability to dynamic field strength changes. For example, in partial discharge monitoring, transient field strength signals may only last for a few microseconds, and the hysteresis response characteristics of traditional materials can easily lead to the omission of key defect signals. More importantly, the high excitation threshold is closely related to the material's band structure, doping concentration, and lattice defects, and existing technologies cannot significantly reduce the threshold by simply optimizing the material ratio, making high-precision detection in weak field strength scenarios a long-standing engineering challenge.

[0008] Disadvantages: High excitation threshold (>0.8 kV / mm).

[0009] Cause: The migration of charge carriers in traditional electric field photoluminescence materials (such as zinc copper sulfide dopants) requires overcoming a high potential barrier, and the weak electric field cannot provide enough energy to drive an effective radiative recombination process.

[0010] 2. Limitations of Single-Dimensional Perception: Vector Deficiency in Multi-Dimensional Electric Field Distribution Monitoring

[0011] Most mainstream electric field sensors operate on a single-axis response mode, capable of measuring only the scalar magnitude of electric field strength and unable to simultaneously acquire vector direction information. This limitation is particularly pronounced in complex electromagnetic environments such as ultra-high-voltage power transmission and new energy grid integration. For example, in substations, the electric field distribution may exhibit multidimensional non-uniform characteristics (e.g., the superposition of combined vertical and horizontal field strengths). Single-axis sensors cannot resolve the field strength direction, leading to incomplete monitoring results and difficulty in guiding equipment operation and maintenance decisions. Furthermore, the single-axis response mechanism relies on a fixed-direction excitation structure (e.g., symmetrical electrode arrangement), limiting its geometric design flexibility and making it difficult to adapt to the monitoring needs of complex curved surfaces (e.g., insulator skirts) or dynamic field strength distributions (e.g., transient lightning strike fields). In existing technologies, some research attempts to achieve direction sensing through multi-sensor array splicing, but such methods suffer from high equipment redundancy, high installation complexity, and difficulty in controlling costs. Moreover, data fusion errors between sensors may further reduce overall accuracy.

[0012] Disadvantages: Lacks vector sensing capability (single-axis response only).

[0013] Cause: Existing sensor structures are usually not directionally sensitive, and their response characteristics are independent of the electric field direction or only sensitive to a single direction, making it impossible to analyze the spatial vector distribution of the electric field.

[0014] 3. Finite dynamic range and linearity: accuracy imbalance in wide amplitude scenarios

[0015] Most electric field sensors typically have an effective dynamic range below 0.6 kV / mm and poor linear response characteristics, making it difficult to guarantee measurement accuracy across a wide range of fields (from weak to strong). For example, in ultra-high voltage transmission systems, the field strength can increase abruptly from 0.2 kV / mm (the partial discharge threshold) at the insulator surface to 1.0 kV / mm (normal operation) near the conductor. Traditional sensors, due to their limited dynamic range, require frequent range switching or rely on external gain adjustment circuits, resulting in low measurement efficiency and susceptibility to systematic errors. Furthermore, the linearity of sensors decreases significantly over a wide dynamic range, especially in high field strength regions (>0.8 kV / mm), where oversaturation of the emitted signal can lead to data distortion. For instance, sensors based on zinc sulfide copper dopant exhibit disrupted linear relationships between emission intensity and field strength above 0.8 kV / mm, potentially causing measurement errors exceeding 20%, severely impacting the reliability of fault warnings. The root cause of this problem lies in the nonlinear optical response characteristics of the materials and the dynamic compression effect of the photodetector; existing technologies struggle to simultaneously meet the requirements of low threshold and high dynamic range using a single sensing mode.

[0016] Disadvantages: narrow dynamic range (<0.6 kV / mm) and nonlinear response.

[0017] Causes: (a) The photosensitive unit lacks the ability to adaptively adjust to light emission signals of different intensities. The signal is weak and easily drowned out by noise at low field strength, and the signal is easily saturated and distorted at high field strength; (b) The material itself or the sensing structure may have nonlinear response or saturation effect at high field strength.

[0018] 4. Structural complexity and active dependence: the contradiction between miniaturization and passive design

[0019] Sensors based on electro-optic or piezoelectric effects typically rely on sophisticated mechanical structures (such as rotating parts and waveguides) or external driving circuits, resulting in bulky devices, difficult installation and maintenance, high power consumption, and limited lifespan. This makes them unsuitable for the miniaturized, passive, and flexible contactless sensing requirements of power grid equipment. For example, electro-optic sensors, whose core components include mechanical rotating parts and waveguide structures, not only increase the device weight (>500 g) but also shorten its lifespan (<5 years) due to mechanical wear. Furthermore, they are prone to structural failure in high-temperature (>85℃) or humid outdoor environments. In addition, optical sensors rely on external light sources (such as lasers), with power consumption exceeding 10 W, making wide-area passive monitoring impossible. For instance, in substation power frequency electric field assessment, traditional sensors require the deployment of hundreds of power supply units, leading to a surge in system complexity and maintenance costs. More importantly, existing technologies cannot achieve flexible sensor attachment through micro-nano fabrication processes, which limits their application in curved surface devices (such as GIS cavities) or dynamic components (such as rotating motors), resulting in a significant gap with the requirements of smart grids for high integration and low-intrusion monitoring.

[0020] Disadvantages: Complex structure, active dependencies.

[0021] Cause: It relies on mechanical structures, waveguides or external driving circuits to achieve sensing functions or signal conversion. Summary of the Invention

[0022] This invention addresses the problems existing in the background art by providing a miniature passive electroluminescent electric field sensing patch with vector sensing capability:

[0023] 1. Significantly reduced excitation threshold: By introducing zinc oxide whiskers (ZnOw) with a high aspect ratio (>50:1), the local electric field enhancement effect at their tips and edges is utilized to effectively reduce the potential barrier that carrier migration needs to overcome, and the light emission excitation threshold of the material is reduced to 0.2 kV / mm (75% lower than that of traditional materials), achieving high sensitivity detection of weak electric fields.

[0024] 2. Achieve synchronous sensing of electric field vectors: Design and construct a columnar array of dielectric discontinuities with gradient spacing characteristics (10-50 μm). Utilize the sensitivity difference of the edge field strength distribution to the electric field direction to synchronously and accurately invert the electric field strength (resolution: 0.03 kV / mm) and vector direction (resolution: 5°).

[0025] 3. Expanding dynamic range and ensuring high linearity: A three-level adaptive photosensitive strategy (high sensitivity / standard / high dynamic range mode) is designed to automatically optimize the gain and dynamic range of the photosensitive unit based on the real-time field strength, expanding the effective dynamic range to 1.0 kV / mm and maintaining excellent near-linear response characteristics (R²>0.98) across the entire range, avoiding signal overexposure and distortion.

[0026] 4. Achieve fully passive, miniaturized, and highly reliable sensing: Based on the principle of direct light emission driven by electric field energy, no external light source or driving circuit is required (self-powered); utilize micro-nano fabrication technology (such as photolithography) to achieve sensor miniaturization and structuring; optimize materials and packaging to improve stability and immunity in complex electromagnetic environments (-25℃~85℃, strong interference).

[0027] Technical solution:

[0028] This invention discloses a method for fabricating a miniature passive electroluminescent electric field sensing patch with vector sensing capability, which includes the following steps:

[0029] S1. Preparation of ZnS:Cu@Al2O3 particles;

[0030] S2. Mix 28-32 parts by weight of ZnS:Cu@Al2O3 particles, 4-6 parts by weight of ZnO whiskers, and 95-105 parts by weight of E51 epoxy resin matrix. Add 80-90 parts by weight of MHHPA as a curing agent and 0.5-1.5 parts by weight of DMP-30 as an accelerator. After high-speed stirring and dispersion, the mixture undergoes pre-curing and complete curing to finally form a composite film.

[0031] S3. Based on the composite material film obtained in S2, a sensing patch is prepared using micro-nano lithography technology.

[0032] Preferably, in S2, 30 parts by mass of ZnS:Cu@Al2O3 particles, 5 parts by mass of ZnO whiskers, and 100 parts by mass of E51 epoxy resin matrix are mixed, and 85 parts by mass of MHHPA is added as a curing agent and 1 part by mass of DMP-30 is added as an accelerator. After the mixture is dispersed by high-speed stirring, it undergoes pre-curing and complete curing to finally form a composite film.

[0033] Preferably, ZnS:Cu@Al2O3 particles are obtained through the following steps:

[0034] S1-1. Mix ZnS and CuCl2 powders at a molar ratio of 1:0.02, using methanol as the dispersion medium, and grind until a uniform precursor is formed;

[0035] S1-2. After the mixture is transferred to an alumina crucible, it is sintered in a tube furnace under an argon protective atmosphere to achieve Cu²⁺ lattice substitution of ZnS lattice.

[0036] S1-3. The sintered product is annealed, and then ZnS:Cu particles are obtained by washing, drying and sieving.

[0037] S1-4. To enhance its insulation strength and thermal stability, an Al2O3 insulating layer is coated on its surface using fluidized bed chemical vapor deposition.

[0038] Preferably, the specific steps of S1-4 are as follows: ZnS:Cu particles are suspended in a microfluidic bed, and argon gas containing 5 wt% trimethylaluminum and oxygen gas containing 5 wt% ozone are sequentially introduced at 200°C for 15 minutes to complete the surface modification.

[0039] Preferably, in S1-2, the product is sintered at 1200°C for 2 hours in a tube furnace; in S1-3, the sintered product is annealed in a muffle furnace at 250°C for 40 minutes.

[0040] Preferably, S3 specifically includes:

[0041] S3-1. SU-8-2000 photoresist is uniformly deposited to a thickness of 5 μm using a spin coating process, and then a periodic gradient dielectric discontinuity array is formed by ultraviolet exposure and development processes. The periodic gradient dielectric discontinuity array contains multiple columnar structural units with different geometric parameters. Their diameter, height and spacing vary in a gradient along a specific direction of the array to distinguish them from planar structures, thereby achieving synchronous sensing of the electric field vector direction.

[0042] S3-2. Remove residual photoresist to ensure the cleanliness of the substrate surface;

[0043] S3-3. The prepared composite film is dissolved in cyclohexanone and uniformly deposited on the substrate surface using a spin-coating process to form a fluorescent layer with a thickness of 20 μm.

[0044] S3-4. Finally, the interlayer bonding strength is enhanced by surface activation treatment, and the sample is placed in a vacuum oven for stepped temperature program curing to complete the preparation of the sensing patch.

[0045] In a specific embodiment, in S3-1, in order to obtain a periodic gradient dielectric discontinuity array, electrode patterns are defined on the front and back sides of the substrate, and then FeCl3 solution is used to etch a copper structure and oxygen plasma is used to remove the residue. Subsequently, UV-curable adhesive is coated on the bonding interface, cured by 365 nm UV light, oxygen-free copper rods are implanted and the gaps are filled with nano-silver conductive adhesive. The electrical connection is completed by heat curing at 150°C for 30 minutes.

[0046] Preferably, in S3-3, the composite film is dissolved in cyclohexanone, and the composite material mass percentage is 5 wt%.

[0047] Preferably, in S3-3, the spin coating process involves a rotation speed of 3000 rpm for 60 seconds.

[0048] Preferably, in S3-4, the stepped temperature program curing is specifically: 90℃ for 2 hours and 110℃ for 2 hours.

[0049] This invention also discloses the application of miniature passive electroluminescent electric field sensing patches in in-situ monitoring of the electric field distribution on the surface of key insulating components in power transmission, transformation, distribution and high-voltage equipment, as well as in mapping the three-dimensional electric field vector field inside or around gas-insulated switchgear (GIS), transformers and generators.

[0050] Preferably, the key insulating components include insulators, cable accessories, and bushings.

[0051] Beneficial effects:

[0052] Threshold Breakthrough: By leveraging the local electric field enhancement effect of zinc oxide whiskers, the material's luminescence excitation threshold is reduced to 0.2 kV / mm (75% lower than traditional materials), achieving accurate detection of weak field strength (<0.3 kV / mm) for the first time, making it suitable for high-sensitivity scenarios such as partial discharge monitoring.

[0053] Dual-parameter measurement:

[0054] Field strength resolution: 0.03 kV / mm (5 times higher than traditional methods), weak signal changes are extracted through regional grayscale analysis algorithm;

[0055] Directional resolution: 5° (omnidirectional error <±3%), based on gradient spacing design of dielectric discontinuity array to ensure consistent orientation sensing.

[0056] Wide dynamic range: Through three-level photosensitive modes (0.2-1.0 kV / mm), the dynamic range is extended to 1.0 kV / mm (R²>0.98), covering the full range of monitoring needs from weak field strength to high field strength, and the linearity is better than traditional methods.

[0057] Completely passive operation: No external light source or driving circuit is required. It achieves self-powered monitoring directly through electric field-optical signal conversion, with power consumption approaching zero. It is suitable for wide-area passive monitoring scenarios (such as substation power frequency electric field assessment). Attached Figure Description

[0058] Figure 1 This is a flowchart illustrating the preparation process of ZnS:Cu@Al2O3 particles according to the present invention.

[0059] Figure 2 This is a flowchart illustrating the preparation process of the fluorescent composite material of the present invention.

[0060] Figure 3 This is a flowchart illustrating the fabrication process of the sensing patch for this invention.

[0061] Figure 4 The image shown is a SEM image of the fluorescent composite material in the example.

[0062] Figure 5 The image shows the fluorescence emission characteristics of the composite material in the examples.

[0063] Figure 6 The diagram shows the response characteristics of the wide-angle electric field direction angle and field strength in the embodiment.

[0064] Figure 7 This is an example diagram of a sensing patch under different photosensitive modes in the embodiment. Detailed Implementation

[0065] The present invention will be further described below with reference to embodiments, but the scope of protection of the present invention is not limited thereto:

[0066] Material:

[0067] ZnS (analytical grade), copper chloride (CuCl2, 99%), zinc oxide whiskers (ZnOw, 99.5%), methanol (99.5%), trimethylaluminum solution (1.0 M in hexanes), deionized water (H2O), anhydrous ethanol (99.5%), E51 epoxy resin, methylhexahydrophthalic anhydride (MHHPA, 98%), and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30, 95%) were all purchased from McLin Corporation (China). High-purity argon (≥99%), nitrogen (≥99%), and oxygen (≥99%) were supplied by Shanghai Central Gas Co., Ltd. (China). Ozone was generated on-site using an ATLAS H30 ozone generator. All chemical reagents were used directly without further purification.

[0068] Preparation of ZnS:Cu@Al2O3 particles:

[0069] like Figure 1As shown, ZnS:Cu particles were prepared by solid-state sintering. ZnS and CuCl2 powders were mixed at a stoichiometric ratio of 1:0.02 (molar ratio) and ground in an agate mortar for 2 hours using methanol as the dispersion medium until a uniform precursor was formed. The mixture was then transferred to an alumina crucible and sintered at 1200℃ for 2 hours in a tube furnace (OTF-1200X-S-II) under an argon (Ar) protective atmosphere to achieve Cu²⁺ lattice substitution of the ZnS lattice. The sintered product was annealed in a muffle furnace (SGM·M6 / 10) at 250℃ for 40 minutes, and then ZnS:Cu particles were obtained by washing, drying, and sieving. To enhance its insulation strength and thermal stability, an Al2O3 insulating layer was coated on its surface using fluidized bed chemical vapor deposition (CVD): ZnS:Cu particles were suspended in a microfluidic bed (VFC-LAB MICRO), and argon gas containing 5 wt% trimethylaluminum (TMA) was sequentially introduced at 200℃ for 15 minutes, followed by oxygen gas containing 5 wt% ozone (O3) for 15 minutes to complete the surface modification.

[0070] Preparation of fluorescent composite materials:

[0071] like Figure 2 As shown, 30 parts by mass of ZnS:Cu@Al2O3 particles, 5 parts by mass of ZnO whiskers (ZnOw), and 100 parts by mass of E51 epoxy resin matrix were mixed. 85 parts by mass of MHHPA was added as a curing agent, and 1 part by mass of DMP-30 as an accelerator. After high-speed stirring and dispersion, the mixture was pre-cured (60℃, 2 hours) and fully cured (120℃, 4 hours) in a vacuum oven (TN-JB50), ultimately forming a composite film with a thickness of 200 μm.

[0072] Fabrication of the sensing patch:

[0073] like Figure 3As shown, a sensing patch was fabricated using micro-nano photolithography. First, SU-8-2000 photoresist was uniformly deposited to a thickness of 5 μm using a spin-coating process. Following UV exposure and development, a periodic gradient dielectric discontinuity array (50 μm in diameter, 100 μm spacing) was formed. This array consists of multiple columnar structural units, whose diameter, height, and spacing vary radially along the array, creating a three-dimensional dielectric discontinuity distribution sensitive to the electric field direction, fundamentally different from conventional planar thin film structures. Subsequently, residual photoresist was removed using oxygen plasma treatment to ensure substrate surface cleanliness. Next, the prepared composite material was dissolved in cyclohexanone (5 wt%) and uniformly deposited onto the substrate surface using a spin-coating process (3000 rpm, 60 seconds) to form a 20 μm thick fluorescent layer. Finally, oxygen plasma surface activation treatment was used to enhance interlayer bonding strength, and the sample was placed in a vacuum oven (SC-1012B) for stepped temperature program curing (90℃ for 2 hours and 110℃ for 2 hours) to complete the fabrication of the sensing patch.

[0074] Material and sensor patch characterization:

[0075] Material characterization:

[0076] Field emission scanning electron microscopy (FE-SEM) combined with energy-dispersive X-ray spectroscopy (EDS) analysis showed that the ZnS:Cu@Al2O3 particles exhibited a polyhedral morphology, with a continuous and dense Al2O3 coating layer on the surface. Figure 4 The particles were free of cracks or pores. Quantitative EDS results showed that the Cu doping concentration in the ZnS matrix was 6 at%, confirming the effective lattice substitution of Zn²⁺ sites by Cu²⁺. Statistical analysis showed that the average particle size was 20.5 μm, with a concentrated size distribution and excellent uniformity. Further selective removal of the particle surface using focused ion beam (FIB) etching technology revealed that Zn, S, and Cu were mainly enriched inside the particles, while Al and O were distributed at the coating layer interface, clearly verifying the successful construction of the Al₂O₃ coating layer.

[0077] The zinc oxide whiskers (ZnOw) introduced into the fluorescent composite material exhibit a typical needle-like morphology (aspect ratio > 50:1). Their high aspect ratio structure significantly reduces the excitation threshold of the ZnS:Cu@Al2O3 component through a localized electric field enhancement effect. Infrared spectroscopy further reveals the chemical composition and structural characteristics of the material. The core component of ZnS:Cu shows a stretching vibration peak of the Zn-S bond at 669 cm⁻¹, clearly indicating the presence of the ZnS crystal structure. The characteristic absorption peak of the Al2O3 coating layer is located at 1051 cm⁻¹, corresponding to the stretching vibration of the Al-O bond, directly verifying the successful construction of the alumina coating layer. Furthermore, the absorption peaks at 3447 cm⁻¹ and 1629 cm⁻¹ are attributed to the -OH stretching vibration and HOH bending vibration, respectively, possibly originating from the lattice hydroxyl groups of Al2O3. The characteristic peaks of ZnOw are the stretching vibrations of the Zn-O bond (506 and 427 cm⁻¹), corresponding to the lattice vibration modes of ZnO, proving the introduction of ZnOw.

[0078] The system combining integrating sphere spectroscopy with fluorescence microscopy showed that, under AC electric field excitation, the material emitted green fluorescence centered at 508 nm. Figure 5 The fluorescence exhibits a full width at half maximum (FWHM) of approximately 80 nm and CIE 1931 chromaticity coordinates of (0.162, 0.403), demonstrating excellent color stability. This fluorescence originates from energy level transitions induced by the periodic charge movement of Cu²⁺ ions in ZnS:Cu: under an alternating electric field, charge carriers undergo directional migration, leading to dynamic changes in the local electric field around Cu²⁺. This, in turn, triggers 4d orbital electrons to transition to the conduction band or valence band, releasing photons of specific wavelengths through radiative recombination.

[0079] The response of the material's fluorescence intensity L to the applied electric field intensity E follows the following empirical formula:

[0080]

[0081] Where L0 is the fluorescence constant and E0 is the electric field strength constant, both of which depend on the intrinsic properties of the material (such as filler particle size and doping concentration). Comparative experiments show that the fluorescence intensity of the composite material containing ZnOw filler is increased by about 20% compared with pure ZnS:Cu@Al2O3 particles. This indicates that the addition of ZnOw not only enhances the fluorescence efficiency of the material but also improves its response sensitivity and lowers the excitation threshold. Furthermore, after reaching the threshold field strength, the fluorescence intensity of the composite material exhibits a good near-linear relationship with the electric field strength (R0). 2 >0.99).

[0082] Sensory patch representation:

[0083] The miniature passive electroluminescent sensing patch designed in this application achieves high-precision decoupling of the direction and intensity of the spatial electric field through a gradient dielectric discontinuity array structure. This structure utilizes the field enhancement effect at the edges of the gradient dielectric discontinuity to generate differentiated fluorescence responses within specific sensing units from electric fields at different orientations. For example... Figure 6 As shown, by building a standardized electric field test platform, applying an electric field with controllable direction and intensity, and acquiring fluorescence images, the spatial resolution capability of the sensing patch was verified.

[0084] (1) Central axis sensing unit: It is most sensitive to the electric field perpendicular to the patch surface, and the luminous intensity reaches its peak in the vertical direction;

[0085] (2) Outer ring sensing unit: It has the maximum response to the horizontal electric field, and its fluorescence intensity increases with the increase of the horizontal field strength;

[0086] (3) Inner ring sensing unit: It exhibits the strongest direction resolution characteristics under the action of a 45° tilted electric field, and the difference in luminous intensity between its upper and lower regions is highly consistent with the electric field vector projection.

[0087] COMSOL Multiphysics simulations show that the gradient dielectric discontinuity structure amplifies the electric field distribution, causing differentiated responses (error <5%) in different directions within a specific sensing unit. The experimental data and simulation results are in high agreement, further validating the scientific validity and feasibility of this design for decoupling the spatial electric field.

[0088] To comprehensively evaluate the performance of the sensing patch over a wide angle range, its response characteristics were tested under electric field direction angle variations of 0-90° and electric field strength variations of 1.0 kV / mm. Fluorescence images showed that as the electric field direction angle increased from 0° to 90°, the central, outer, and inner sensing units exhibited unique response modes to vertical, horizontal, and tilted electric fields, respectively. Quantitative analysis indicated that as the electric field strength gradually increased from 0.2 kV / mm to 1.0 kV / mm, the luminescence intensity of each sensing unit showed an exponential growth trend, verifying the patch's high sensitivity under low threshold conditions. Under a 45° tilted electric field condition, the difference in luminescence intensity between the upper and lower regions of the inner unit reached its maximum, demonstrating its superior detection capability for tilted electric fields compared to traditional two-dimensional sensing structures.

[0089] During the experiment, it was observed that the relative luminescence intensity among the sensing units fluctuated regularly with the change of electric field angle, which is completely consistent with the theoretical model based on the edge field enhancement effect of gradient dielectric discontinuity. Under the action of electric fields at 0° and 90°, the central axis and outer ring units showed the strongest luminescence response, corresponding to the concentration of maximum field strength in the vertical and horizontal directions, respectively. Under the action of electric field at 45°, the asymmetric luminescence characteristics of the inner ring units reached the peak, and its response mechanism originated from the gradient distribution amplification effect of the gradient dielectric discontinuity on the oblique electric field.

[0090] To quantify the azimuth response characteristics of the sensing patch, a rotation test method was used to evaluate its uniformity at different azimuth angles (φ and θ). Specifically:

[0091] (1) Azimuth angle φ test: The patch was rotated 360° around the Z-axis, and the average gray value change of the entire area was recorded. The results showed that the gray value fluctuation range at each angle was <3%, which verified the structural symmetry and response consistency of the patch in the full omnidirectional angle range;

[0092] (2) Polar Angle θ Test: The maximum brightness variation of the central axis, inner ring, and outer ring sensing units in the range of θ=0-90° was analyzed respectively. When the central axis unit is at θ=0° (vertical direction), its relative gray value reaches its peak (100%); while it drops to its lowest (0%) at θ=90° (horizontal direction), forming a significant contrast. Conversely, the outer ring unit reaches its peak luminous intensity (100%) at θ=90°, and drops to its lowest (10%) at θ=0°. The inner ring unit exhibits different characteristics: its relative gray value difference is approximately zero at θ=0° (vertical direction) and θ=90° (horizontal direction), while it reaches its maximum value at θ=45°. This complementary and differentiated response characteristic composed of the central axis, inner ring, and outer ring units proves that the sensing patch can achieve vector reconstruction of the spatial electric field through multi-unit collaboration.

[0093] To address the data distortion caused by overexposure of fluorescence signals under high field strength and to ensure that the sensing patch maintains a stable near-linear response over a wide dynamic range, this study introduces three photosensitive modes ( Figure 7 ):

[0094] (1) Low electric field mode (0.33-0.67 kV / mm): A high-sensitivity detector is used to capture changes in weak fluorescence signals, which is suitable for electric field monitoring in low field strength scenarios;

[0095] (2) Medium electric field mode (0.53-0.87 kV / mm): Balances sensitivity and dynamic range to ensure stable and reliable measurement results under normal operating conditions;

[0096] (3) High electric field mode (0.6-1.0 kV / mm): Enables a detector with low sensitivity but high dynamic range, effectively suppressing nonlinear distortion of excessively strong signals, while maintaining accurate resolution of high field strength.

[0097] By comparing and analyzing the experimental data under these three photosensitive modes, we found that a stable near-linear response (R² > 0.98) can be maintained between the fluorescence signal and the electric field intensity in all three electric field intensity ranges. This strategy not only expands the effective measurement range of the sensing patch but also improves its adaptability and reliability in different application scenarios, thus meeting various needs from basic research to industrial applications.

[0098] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.

Claims

1. A method for fabricating a miniature passive electroluminescent electric field sensing patch with vector sensing capability, characterized in that... It includes the following steps: S1. Preparation of ZnS:Cu@Al2O3 particles; S2. Mix 28-32 parts by weight of ZnS:Cu@Al2O3 particles, 4-6 parts by weight of ZnO whiskers, and 95-105 parts by weight of E51 epoxy resin matrix. Add 80-90 parts by weight of MHHPA as a curing agent and 0.5-1.5 parts by weight of DMP-30 as an accelerator. After high-speed stirring and dispersion, the mixture undergoes pre-curing and complete curing to finally form a composite film. S3. Based on the composite material film obtained in S2, a sensing patch is prepared using micro-nano lithography technology.

2. The method according to claim 1, characterized in that... ZnS:Cu@Al2O3 particles are obtained through the following steps: S1-1. Mix ZnS and CuCl2 powders at a molar ratio of 1:0.02, using methanol as the dispersion medium, and grind until a uniform precursor is formed; S1-2. After the mixture is transferred to an alumina crucible, it is sintered in a tube furnace under an argon protective atmosphere to achieve Cu²⁺ lattice substitution of ZnS lattice. S1-3. The sintered product is annealed, and then ZnS:Cu particles are obtained by washing, drying and sieving. S1-4. To enhance its insulation strength and thermal stability, an Al2O3 insulating layer is coated on its surface using fluidized bed chemical vapor deposition.

3. The method according to claim 2, characterized in that... The specific steps of S1-4 are as follows: ZnS:Cu particles are suspended in a microfluidic bed, and argon gas containing 5 wt% trimethylaluminum is sequentially introduced for 15 minutes and oxygen gas containing 5 wt% ozone for 15 minutes at 200℃ to complete the surface modification.

4. The method according to claim 2, characterized in that: In S1-2, the product is sintered at 1200℃ for 2 hours in a tube furnace; in S1-3, the sintered product is annealed in a muffle furnace at 250℃ for 40 minutes.

5. The method according to claim 2, characterized in that, S3 specifically includes: S3-1. SU-8-2000 photoresist is uniformly deposited to a thickness of 5 μm using a spin coating process, and then a periodic gradient dielectric discontinuity array is formed by UV exposure and development processes. S3-2. Remove residual photoresist through oxygen plasma treatment to ensure the cleanliness of the substrate surface; S3-3. The prepared composite film is dissolved in cyclohexanone and uniformly deposited on the substrate surface using a spin coating process to form a fluorescent layer with a thickness of 20 μm. S3-4. Finally, the interlayer bonding strength is enhanced by surface activation treatment, and the sample is placed in a vacuum oven for stepped temperature program curing to complete the preparation of the sensing patch.

6. The method according to claim 5, characterized in that, In S3-3, the composite film is dissolved in cyclohexanone, and the mass percentage of the composite material is 5 wt%.

7. The method according to claim 5, characterized in that, In S3-3, the spin coating process involves a rotation speed of 3000 rpm for 60 seconds.

8. The method according to claim 5, characterized in that, In S3-4, the step-temperature programmable curing is specifically: 90℃ for 2 hours and 110℃ for 2 hours.

9. The application of a miniature passive electroluminescent electric field sensing patch prepared by any one of claims 1-8 in in-situ monitoring of the electric field distribution on the surface of key insulating components in power transmission, substation, distribution and high-voltage equipment, as well as in mapping the three-dimensional electric field vector field inside or around gas-insulated combined electrical equipment (GIS), transformers, generators.

10. The application according to claim 9, characterized in that... The key insulating components include insulators, cable accessories, and bushings.